Heuristic evaluation of interface usability for a web-based OPAC - Mansor, Yushiana; Abdul Rani, Widyawati (Emerald Group Publishing Ltd., 2007)
Purpose - The purpose of this paper is to investigate the usability of a web-based OPAC (WebPAC) user interface at the International Islamic University Malaysia (IIUM). It also looks at the applicability of heuristic evaluation in designing a user-centered WebPAC interface. Design/methodology/approach - Based on Nielsen's ten usability heuristic principles, the study focuses on three heuristics only, i.e. aesthetic and minimalist design, match between interface and the real world, and visibility of interface status. Findings - Results of the study found that the WebPAC interface conforms to at least 70 percent usability properties prescribed. Usability problems violated in the interface were identified. Practical implications - The study suggests that heuristic evaluation is applicable in libraries to asses the usability of user interface for online catalogs. Originality/value - Heuristic evaluation could assist libraries in designing user-centered interface for online catalogs.